The Effect of Visual Merchandising, Product Display and Store Atmosphere on Impulse Buying Customers of Ramayana Malang - Reza Suriansha; Hamzah Bustomi; Erna Herlina; Yusuf Iskandar; Zeze Zakaria Hamzah (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of visual merchandising, product display and store atmosphere on impulse buying. This research was conducted at the Ramayana department store, Jl. MT. Haryono, Dinoyo, Malang City, East Java. The sampling technique of this research is non-probability sampling and purposive sampling of 50 respondents. The analysis technique uses multiple linear regression analysis, F test, t test and coefficient of determination. The results of data analysis show that the activity. The results of this study indicate that visual merchandising, product display and store atmosphere have a simultaneous influence on Impulse Buying. Overall, visual merchandising, product displays and store atmosphere have an effect on Impulse Buying by 84.0% and the remaining 16.0% is influenced by other variables.